Deformation-related microstructures in magmatic zircon and implications for diffusion - Reddy, Steven; Timms, Nicholas Eric; Hamilton, P. Joseph; Smyth, Helen (Springer, 2009)
An undeformed glomeroporphyritic andesite from Java, Indonesia, contains zoned plagioclase and amphibole glomerocrysts in a fine-grained groundmass and records a complex history of adcumulate formation and subsequent disaggregation by externally derived melts. A suite of xenocrystic zircon records Proterozoic and Archaean dates whilst a second population of zoned, euhedral, igneous zircon yields a SHRIMP crystallisation age of 9.3 0.2 Ma. Quantitative microstructural analysis (via electron backscatter diffraction - EBSD) show no deformation in the inherited xenocrysts, but intragrain orientation variations of up to c.30 in 80% of the young zircon population. These variations are typically accommodated by both progressive crystallographic bending and discrete low angle boundaries that overprint growth zoning. Dispersion of crystallographic orientations are dominantly by rotation about an axis parallel to the zircon c-axis [001], which is coincident with the dominant orientation of misorientation axes of adjacent analysis points in EBSD maps. Less common <100> misorientation axes account for minor components of crystallographic dispersion. These observations are consistent with zircon deformation by dislocation creep and the formation of tilt and twist boundaries associated with the operation of <001>{100} and <100>{010} slip systems.The restriction of deformation microstructures to large glomerocrysts and the young magmatic zirconpopulation, and the absence of deformation within the host igneous rock and inherited zircon grains, indicatethat zircon deformation took place within a low-melt fraction (<5% melt), mid - lower crustal cumulate prior tofragmentation during magmatic disaggregation and entrainment of xenocrystic zircons during magmaticdecompression. Tectonic stresses within the compressional Sunda Arc at the time of magmatism are consideredto be the probable driver for low-strain deformation of the cumulate in the late stages of initial crystallisation.These results provide the first evidence of crystal plastic dislocation creep in zircon associated with magmatic crystallisation and indicate that the development of crystal-plastic microstructures in zircon is not restricted to high-strain rocks. Such microstructures have previously been shown to enhance bulk diffusion of trace elements (U, Th and REE) in zircon. The development of deformation microstructures, and therefore multiple diffusion pathways in zircon in the magmatic environment, has significant implications for the interpretation of geochemical data from igneous zircon and the trace element budgets of melts due to the potential enhancement of bulk diffusion and dissolution rates.